2017
DOI: 10.3233/jad-160970
|View full text |Cite
|
Sign up to set email alerts
|

Subjective Cognitive Complaints in Cognitively Healthy Older Adults and Their Relationship to Cognitive Performance and Depressive Symptoms

Abstract: We identified some cognitive complaints that were very common in our sample. Overall, a higher number of SCCs in well cognitively functioning individuals was most closely related to depressive symptomatology, while some specific complaints reflected lower memory performance and should be considered when screening for people at risk of cognitive decline.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

7
43
0
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 64 publications
(51 citation statements)
references
References 42 publications
7
43
0
1
Order By: Relevance
“…Indeed, Hispanics with SCD [2] as well as Hispanics who endorse more items on a depression scale [23] have an increased risk of developing cognitive decline in the future. Importantly, the present results replicate previous findings in non-Hispanic White community and clinic-based samples [8, 9, 24], contributing to the SCD-I working group’s recommendation to investigate whether or not SCD manifests differently in various racial and ethnic backgrounds.…”
Section: Discussionsupporting
confidence: 87%
See 1 more Smart Citation
“…Indeed, Hispanics with SCD [2] as well as Hispanics who endorse more items on a depression scale [23] have an increased risk of developing cognitive decline in the future. Importantly, the present results replicate previous findings in non-Hispanic White community and clinic-based samples [8, 9, 24], contributing to the SCD-I working group’s recommendation to investigate whether or not SCD manifests differently in various racial and ethnic backgrounds.…”
Section: Discussionsupporting
confidence: 87%
“…Third, we cannot address the value that SCD may hold in predicting future cognitive decline in this sample due to the cross-sectional nature of this study. Several research studies have observed minimal cross-sectional associations between SCD reporting and cognitive performance [5, 8, 9, 24], while others have consistently found associations between SCD reporting and biomarkers of Alzheimer’s disease and future cognitive decline [25, 3133], although this is not always the case [34, 35]. Our current results replicate and extend previous cross-sectional findings in non-Hispanic Whites to a group of Hispanic older adults; however, additional research continues to be needed to determine the value of SCD in predicting future cognitive changes in older Hispanics.…”
Section: Discussionmentioning
confidence: 99%
“…В настоящем исследовании частота жалоб на снижение памяти у больных трудоспособного возраста составила около 45%. По данным литературы [13,14] от 20 до 50% пациентов старше 50 лет жалуются на забывчивость и затруднения в подборе слов.…”
Section: Discussionunclassified
“…Cognitively intact older adults who report memory problems may be up to twice as likely to develop cognitive impairment 5 to 10 years later, and multiple studies have found accelerated transitions into AD and other dementias after impairment onset . However, some studies demonstrate no association between self‐reported memory and cognitive decline, and others find that memory complaints may be more strongly associated with affective symptoms or personality than with objective cognition . One factor that may contribute to cognitive decline risk is co‐occurring anxiety symptoms.…”
Section: Introductionmentioning
confidence: 99%
“…[8][9][10] However, some studies demonstrate no association between self-reported memory and cognitive decline, 11,12 and others find that memory complaints may be more strongly associated with affective symptoms or personality than with objective cognition. [13][14][15] One factor that may contribute to cognitive decline risk is co-occurring anxiety symptoms. Anxiety increases the risk for cognitive decline and AD 16 and may mediate the association between memory complaints and cognitive decline in some older adults.…”
mentioning
confidence: 99%